Upaya pemberantasan kutu rambut santri, pelatihan produksi sampo antiketombe dan wirausaha barbershop pesantren - Viddy Agustian Rosyidi; Ika Rahmawati Sutejo (INDRA: Jurnal Pengabdian kepada Masyarakat, 2021)
Head lice, dandruff and other scalp diseases are still one of the main problems of the students at the Nurul Qarnain boarding school. Factors that influence the development of disease are poor personal hygiene due to the students' lack of understanding of this disease. Anti-dandruff shampoo, is expensive and is insufficient to treat head lice problem among students. Furthermore, the absence of professional barbers in the boarding school environment is also one of the factors that triggered this problem. The results of this activity are increased knowledge of students about hair health from 58.8% to 98.24% and the ability and skills of students to make anti-dandruff shampoo and hair cutting. This is expected to increase awareness and ability to care for hair and provide added value to the economy.